A study of how UTAR Sungai Long Campus undergraduates utilise social media in the search of internship opportunities - Lim, Yu Wei (2023)
In the era of technology, social media has become a tool among undergraduate students to search for internship opportunities. Most of them have been exposed to the usage of social media since young, their purposes of usage change accordingly to their different stages in their lives. It is a requirement for university students to undergo internship programmes within their study. The objective of this research is to find out how Universiti Tunku Abdul Rahman (UTAR) Sungai Long campus undergraduates utilise social media in searching for internship opportunities. The quantitative approach was applied by distributing online questionnaire to 100 undergraduate students from UTAR Sungai Long campus. The result of the research concludes that UTAR Sungai Long campus undergraduate students prefer using social media to seek for internships and JobStreet is their favourite platform, and the most used function is browsing companies’ profiles.